Evaluation of a BCC alloy as metal hydride compressor via 100 MPa-class high-pressure hydrogen apparatus. (23rd April 2019) - Goshome, Kiyotaka; Endo, Naruki; Tetsuhiko, Maeda
Abstract: In the study presented here, an apparatus that correctly measured pressure–composition isotherms (PCi) at high pressures (up to 100 MPa) and temperatures (up to 200 °C) was developed. The PCi characteristics of a vanadium–titanium–chromium alloy at high pressure and temperature were examined with the apparatus to develop a metal hydride (MH) compressor. It was revealed that it is possible to use a 40 V20Ti40Cr (at%) alloy with a heat source below 200 °C for hydrogen compression in the approximate range of 2.1–30.0 MPa. The compressed content reached approximately 1.8 wt%, which is almost the same as the reversible hydrogen capacity at 20 °C. Highlights: BCC metal hydrides are potential materials for hydrogen compression. Pressure–composition isotherms (PCi) of a BCC VTiCr alloy (VTiCr) were obtained. High-pressure hydrogen apparatus was developed to measure PCi. Hydrogen compression between 2.1 and 30 MPa was possible with VTiCr at 200 °C.